Impact of Intrahost NS5 Nucleotide Variations on Dengue Virus Replication - Cheng, Dayna; Huang, Sheng-Wen; Chin, Wei-Xin; Hung, Su-Jhen; Tsai, Huey-Pin; Chu, Justin Jang Hann; Chao, Chiao-Hsuan; Wang, Jen-Ren (Frontiers in Microbiology, 2022)
Due to the nature of RNA viruses, their high mutation rates produce a population of closely related but genetically diverse viruses, termed quasispecies. To determine the role of quasispecies in DENV disease severity, 22 isolates (10 from mild cases, 12 from fatal cases) were obtained, amplified, and sequenced with Next Generation Sequencing (NGS) using the Illumina MiSeq platform. Using variation calling, unique wildtype nucleotide positions were selected and analyzed for variant nucleotides between mild and fatal cases. The analysis of variant nucleotides between mild and fatal cases showed 6 positions with a significant difference of p<0.05 with 1 position in the structural region, and 5 positions in the non-structural (NS) regions. All variations were found to have a higher percentage in fatal cases. To further investigate the genetic changes that affect the virus's properties, reverse genetics viruses containing substitutions with the variations were generated and viral growth properties were examined. We found that the virus variant rgNS5-T7812G (G81G) had higher replication rates in both BHK-21 and Vero cells while rgNS5-C9420A (A617A) had a higher replication rate only in BHK-21 cells compared to wildtype virus. Both variants were considered temperature sensitive whereby the viral titers of the variants were relatively lower at 39oC, but was higher at 35oC and 37oC. Additionally, the variants were thermally stable compared to wildtype at temperatures of 29oC, 37oC, and 39oC. In conclusion, viral quasispecies found in isolates from the 2015 DENV epidemic, resulted in variations with significant difference between mild and fatal cases. These variations, NS5-T7812G (G81G) and NS5-C9420A (A617A), affect viral properties which may play a role in the virulence of DENV.